2022
DOI: 10.55730/1300-0527.3484
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study and dyeing performance of as-synthesized azo heterocyclic monomeric, polymeric, and commercial disperse dyes

Abstract: In this study poly (4-nitrophenylazo-3-aminopyridine - formaldehyde) (PNAAP-F) and poly (4-nitroarylazo-3-chloro-6-hydroxypyridine - formaldehyde) (NAACHP-F) were synthesized via diazotization, coupling and polycondensation reactions. The structural properties of the as-synthesized dyes were acquired using Fourier-transform infrared spectroscopy (FTIR) and UV-visible absorption maxima and their color, yield, melting point, solubility, and viscosity were determined via standard methods. UV-visible and FTIR resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This coincides with the findings by [44], where it was reported that NH 4 + −N removal efficiency increased with decreasing HRT because the decrease of HRT coincides with the increase of hydraulic loading rate which can interfere with the biodegradation and interaction time between the microorganisms and the substrate and subsequently cause an incomplete biodegradation. A similar result was observed by [45], where it was noted that NH 4 + −N removal was in the range of 99.42-77.58% with HRT decreasing in the range of 4,3, 2, and 1 day in a biological treatment system. Thus, it was concluded that short HRT alters the dynamic balance, composition, and spatial distribution of the ecological structure of microbial systems and could decrease removal efficiency.…”
Section: Fesemsupporting
confidence: 86%
“…This coincides with the findings by [44], where it was reported that NH 4 + −N removal efficiency increased with decreasing HRT because the decrease of HRT coincides with the increase of hydraulic loading rate which can interfere with the biodegradation and interaction time between the microorganisms and the substrate and subsequently cause an incomplete biodegradation. A similar result was observed by [45], where it was noted that NH 4 + −N removal was in the range of 99.42-77.58% with HRT decreasing in the range of 4,3, 2, and 1 day in a biological treatment system. Thus, it was concluded that short HRT alters the dynamic balance, composition, and spatial distribution of the ecological structure of microbial systems and could decrease removal efficiency.…”
Section: Fesemsupporting
confidence: 86%
“…This indicates that for advantageous (favorable) adsorption, 0 < 𝑅 < 1, 𝑅 > 1 denotes unfavorable adsorption, 𝑅 = 1 denotes linear adsorption, and 𝑅 = 0 denotes irreversible adsorption. According to study estimates, 𝑅 varied between 0.062 and 0.068, indicating that the adsorption is advantageous [41][42][43][44][45][46][47][48]. This indicates that for advantageous (favorable) adsorption, 0 < R L < 1, R L > 1 denotes unfavorable adsorption, R L = 1 denotes linear adsorption, and R L = 0 denotes irreversible adsorption.…”
Section: Isotherms Of Adsorptionmentioning
confidence: 99%
“…This indicates that for advantageous (favorable) adsorption, 0 < R L < 1, R L > 1 denotes unfavorable adsorption, R L = 1 denotes linear adsorption, and R L = 0 denotes irreversible adsorption. According to study estimates, R L varied between 0.062 and 0.068, indicating that the adsorption is advantageous [41][42][43][44][45][46][47][48].…”
Section: Isotherms Of Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological methods may be a good choice, but it is impossible to reach the regulatory limitations of discharge for this effluent with current procedures [10]. Scientists have been paying close attention to the use of combined activated sludge and biosorption techniques since waste management systems began to change globally owing to the imminent danger of global climate change and other environmental challenges [11,12].…”
Section: Introductionmentioning
confidence: 99%